Comparative Genomic Analysis Reveals a Diverse Repertoire of Genes Involved in Prokaryote-Eukaryote Interactions within the Pseudovibrio Genus - Romano, Stefano; Fernàndez-Guerra, Antonio; Reen, F. Jerry; Glöckner, Frank O.; Crowley, Susan P.; O'Sullivan, Orla; Cotter, Paul D.; Adams, Claire; Dobson, Alan D. W.; O'Gara, Fergal (Frontiers in Microbiology, 2016)
Strains of the Pseudovibrio genus have been detected worldwide, mainly as part of bacterial communities associated with marine invertebrates, particularly sponges. This recurrent association has been considered as an indication of a symbiotic relationship between these microbes and their host. Until recently, the availability of only two genomes, belonging to closely related strains, has limited the knowledge on the genomic and physiological features of the genus to a single phylogenetic lineage. Here we present 10 newly sequenced genomes of Pseudovibrio strains isolated from marine sponges from the west coast of Ireland, and including the other two publicly available genomes we performed an extensive comparative genomic analysis. Homogeneity was apparent in terms of both the orthologous genes and the metabolic features shared amongst the 12 strains. At the genomic level, a key physiological difference observed amongst the isolates was the presence only in strain P. axinellae AD2 of genes encoding proteins involved in assimilatory nitrate reduction, which was then proved experimentally. We then focused on studying those systems known to be involved in the interactions with eukaryotic and prokaryotic cells. This analysis revealed that the genus harbors a large diversity of toxin-like proteins, secretion systems and their potential effectors. Their distribution in the genus was not always consistent with the phylogenetic relationship of the strains. Finally, our analyses identified new genomic islands encoding potential toxin-immunity systems, previously unknown in the genus. Our analyses shed new light on the Pseudovibrio genus, indicating a large diversity of both metabolic features and systems for interacting with the host. The diversity in both distribution and abundance of these systems amongst the strains underlines how metabolically and phylogenetically similar bacteria may use different strategies to interact with the host and find a niche within its microbiota. Our data suggest the presence of a sponge-specific lineage of Pseudovibrio. The reduction in genome size and the loss of some systems potentially used to successfully enter the host, leads to the hypothesis that P. axinellae strain AD2 may be a lineage that presents an ancient association with the host and that may be vertically transmitted to the progeny.